Giant cell arteritis of the female genital tract with temporal arteritis. Issue 7 (July 1992) - Lhote, F; Mainguene, C; Griselle-Wiseler, V; Fior, R; Feintuch, M J; Royer, I; Jarrousse, B; Amouroux, J; Guillevin, L
Abstract : The clinical and pathological features of a patient with giant cell arteritis of the uterus and ovaries are described. A 61 year old woman had fever and weight loss over a period of eight months. A hysterectomy with bilateral salpingo-oophorectomy was performed for a large cystic ovarian mass. Histological examination showed a benign ovarian cyst and unexpected giant cell arteritis affecting numerous small to medium sized arteries in the ovaries and myometrium. The diagnosis of temporal arteritis was confirmed by a random temporal artery biopsy, despite the absence of symptoms of temporal arteritis. This observation is compared with previously reported cases and the relation between granulomatous arteritis of the genital tract and temporal arteritis is discussed. The main differential diagnosis in this localisation was represented by Wegener's granulomatosis and periarteritis nodosa.